The Miracles of Al-Quran: Al-Quran as a Grace and Guidance of Muslims - Djamdjuri, Dewi Suriyani; kamilah, Iil Hilyatul (Asatiza: Jurnal Pendidikan, 2021)
This paper aimed at explaining the functions of the Al-Quran as a blessing and guidance for mankind, especially for Muslims in this world. It is the duty of the scholars at any time to find the existing arguments and process them with the right to provide legal certainty to problems that arise in time. To know the law of a problem based on the most appropriate arguments, it is necessary to update the right one, namely the Al-Quran because it has covered all problems in life. The result of this study showed that the Al-Quran is a light that appears in the hearts of Muslims, which breaks the flower of faith, appears in life so that it becomes light, rises to the heavens of mankind so that a plan of peace and guidance appears to humans to introduce their status and obligations, then lead to the straight path. This statement means that Al-Quran is guidance for humans. The function of Al-Quran globally is as a principle of the Islamic religion, in which there is the principle of every science in human language past and present and the future. Al-Quran is more than just a Holy Book, it is also a very useful book or a perfect reference.